In vivo behavior of [64Cu]NOTA-terpyridine platinum, a novel chemo-radio-theranostic agent for imaging, and therapy of colorectal cancer - Khosravifarsani, Meysam; Ait-Mohand, Samia; Paquette, Benoit; Sanche, Léon; Guérin, Brigitte (Frontiers in Medicine, 2022)
To overcome resistance to chemotherapy for colorectal cancer, we propose to validate in vivo a novel terpyridine-platinum (TP) compound radiolabeled with the radio-theranostic isotope 64Cu. In vivo stability, biodistribution, PET imaging, tumor growth delay, toxicity and dosimetry of [64Cu]NOTA-C3-TP were determined. The current experimental studies show that [64Cu]NOTA-C3-TP is stable in vivo, rapidly eliminated by the kidneys and has a promising tumor uptake ranging from 1.8 ± 0.4 to 3.0 ± 0.2 %ID/g over 48 h. [64Cu]NOTA-C3-TP retarded tumor growth by up to 6 ± 2.0 days and improved survival relative to vehicle and non-radioactive [NatCu]NOTA-C3-TP over 17 days of tumor growth observation. This effect was obtained with only 0.4 nmol i.v. injection of [64Cu]NOTA-C3-TP, which delivers 3.4 ± 0.3 Gy tumoral absorbed dose. No evidence of toxicity, by weight loss or mortality was revealed. These findings confirm the high potential of [64Cu]NOTA-TP as a novel radio-theranostic agent.